2021
DOI: 10.33549/physiolres.934647
|View full text |Cite
|
Sign up to set email alerts
|

CCR5Δ32 Deletion as a Protective Factor in Czech First-Wave COVID-19 Subjects

Abstract: Infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease (COVID-19), has spread widely around the globe. Significant inter-individual differences have been observed during the course of the infection, which suggests that genetic susceptibility may be a contributing factor. CC chemokine receptor 5 (CCR5), which acts as a co-receptor for the entry of HIV-1 into cells, is promising candidate whose can have an influence on SARS-CoV-2 infection. A genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…Thus, countries with higher deletion frequency could show the highest infection and COVID-19 mortality rates [20] , [21] . Our work and others did not support this conclusion [19] . Moreover, Spain has one of the lowest CCR5- Δ32 frequencies while having one of the highest worldwide infection and mortality rates ( https://www.worldometers.info/coronavirus ) (suppl.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…Thus, countries with higher deletion frequency could show the highest infection and COVID-19 mortality rates [20] , [21] . Our work and others did not support this conclusion [19] . Moreover, Spain has one of the lowest CCR5- Δ32 frequencies while having one of the highest worldwide infection and mortality rates ( https://www.worldometers.info/coronavirus ) (suppl.…”
Section: Resultscontrasting
confidence: 74%
“…Another study genotyped416 Czech first-wave SARS-CoV-2-positive infection survivors (164 asymptomatic and 252 symptomatic) and compared them with a population cohort (n=2,404). The authors found a significantly higher CCR5 Δ32 frequency in asymptomatic SARS-CoV-2-positive compared to COVID-19-symptomatic patients, and concluded the CCR5 deletion might predict the severity of SARS-CoV-2 infection [19] .…”
Section: Resultsmentioning
confidence: 95%
“…Using RT-PCR and the TaqMan assay (ID − C_3084793_20), we analysed the APOE4 polymorphism (rs429358) in a group of 408 Czech first-wave (approximately March 2020–June 2020) SARS-CoV-2 PCR-positive (PCR test) subjects (54.7% females, mean age 44 ± 15 years, diabetes prevalence 7.8%, hypertension prevalence 13.3%). Of this total number, 164 were asymptomatic and 244 symptomatic [ 4 ]. All patients were confirmed SARS-CoV-2-negative by the time of sample collection in July 2020.…”
mentioning
confidence: 99%
“…C-C Motif Chemokine Receptor 5 (CCR5) forms a significant RR ERC with XCR1 as well. Several studies have implicated CCR5 variation and expression to be associated with COVID-19 severity (Gómez et al, 2020; Hubacek et al, 2021; Kasela et al, 2021), while others have not (Bernas et al, 2021). TNFSF15 is a third immune response protein in the XCR1 RR subnetwork that shows elevated expression in patients with severe COVID-19 (Jain et al, 2021).…”
Section: Resultsmentioning
confidence: 99%